Regulating capital flows in emerging markets: The IMF and the global financial crisis - Kevin Gallagher; Yuan Tian (Review of Development Finance, 2017)
In the wake of the financial crisis the International Monetary Fund (IMF) began to publicly express support for what have traditionally been referred to as 'capital controls'. This paper empirically examines the extent to which the change in IMF discourse on these matters has resulted in significant changes in actual IMF policy advice. By creating and analyzing a database of IMF Article IV reports, we examine whether the financial crisis had an independent impact on IMF support for capital controls. We find that the IMF's level of support for capital controls has increased as a result of the crisis and as the vulnerabilities associated with capital flows accentuate.
Keywords: 650; IMF; Emerging Markets; Capital Flow Management Measures